Tunnel Junctions for III-V Multijunction Solar Cells Review - Peter Colter; Brandon Hagar; Salah Bedair (Crystals, 2018)
Tunnel Junctions, as addressed in this review, are conductive, optically transparent semiconductor layers used to join different semiconductor materials in order to increase overall device efficiency. The first monolithic multi-junction solar cell was grown in 1980 at NCSU and utilized an AlGaAs/AlGaAs tunnel junction. In the last 4 decades both the development and analysis of tunnel junction structures and their application to multi-junction solar cells has resulted in significant performance gains. In this review we will first make note of significant studies of III-V tunnel junction materials and performance, then discuss their incorporation into cells and modeling of their characteristics. A Recent study implicating thermally activated compensation of highly doped semiconductors by native defects rather than dopant diffusion in tunnel junction thermal degradation will be discussed. AlGaAs/InGaP tunnel junctions, showing both high current capability and high transparency (high bandgap), are the current standard for space applications. Of significant note is a variant of this structure containing a quantum well interface showing the best performance to date. This has been studied by several groups and will be discussed at length in order to show a path to future improvements.